Association of Single-Nucleotide Polymorphisms of rs2383206, rs2383207, and rs10757278 With Stroke Risk in the Chinese Population: A Meta-analysis - Hu, Xuemei; Wang, Dongsen; Cui, Chunying; Wu, Qingjian (Frontiers in Genetics, 2022)
Several studies have reported that chromosome 9p21 is significantly associated with ischemic stroke (IS) risk, with the G allele associated with increased risk. However, controversial results have been reported in the literature. We systematically assessed the relationship between stroke and three 9p21 loci (rs2383206, rs2383207, and rs10757278) in this meta-analysis. First, we searched the PubMed and Embase databases for relevant studies. We then calculated odds ratios using the chi-squared test. The evaluation of experimental data was performed using bias tests and sensitivity analyses. We analyzed data from 16 studies involving 18,584 individuals of Chinese ancestry, including 14,033 cases and 14,656 controls. Our results indicated that chromosome 9p21 is significantly associated with IS (odds ratio: 1.15, 95% confidence interval: 1.1–1.20, p < 0.0001). Because the three single-nucleotide polymorphisms (rs2383206, rs2383207, and 10757278) have a linkage disequilibrium relationship, all three may increase the risk of IS.